ALGORITHMS FOR SYNTHESIS OF FUZZY REGULATORS - M.Majidova (Journal of new century innovations, 2022)
Annotations: The influence of the dimension of an a priori set of possible values of the used linguistic variables, as well as the form of the corresponding membership functions on the nature of nonlinear transformations in simply connected fuzzy control models, is studied. The formation of logical-linguistic models of dynamic objects is the most important problem in the methodology of analytical design of fuzzy control systems.